Stocking rate effects on intensive-early stocked bluestem range - Cochran, R.; Smith, E.F.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Based on a six-year study, stocking at 2.5x and 3.0x normal season-long rates for the first half of the growing season with no grazing during the latter half results in individual steer gains that are equal to those under the 2.0x rate. The gain per acre was greatly increased at the higher stocking rates. Grass remaining in early October was 20 percent lower on pastures stocked at the 2.5x and 3.0x rates than at the 2.0x rate. However, there was no trend toward further reductions over the study period. Botanical composition did not change greatly as a result of the different stocking rates. Apparently, Flint Hills bluestem range can be intensive-early stocked at rates higher than the traditional 2.0x rate.
Keywords: Beef; Stocking rate; Bluestem range